The Impact of Mobile-Assisted Language Learning (MALL) on Developing Reading Skills of EFL Learners: A Literature Review - Sadiyeva, Shahnoza Komilovna (The Lingua Spectrum, 2026)
In recent years, the rapid development of mobile technologies has significantly influenced the process of language learning, and Mobile-Assisted Language Learning (MALL) has emerged as an important pedagogical approach within the EFL (English as a Foreign Language) context. This article provides a systematic and critical review of the scientific literature examining the impact of MALL on EFL learners’ reading skills. The findings of the analysis indicate that mobile technologies enhance learners’ motivation, expand their vocabulary, and promote learner autonomy. However, existing studies also highlight several drawbacks of mobile reading, including distraction, superficial reading, and increased cognitive load, which may hinder deep comprehension. Furthermore, comparative findings between mobile and traditional reading are inconsistent, reflecting the complexity of this research area. The literature review reveals that most existing studies are based on short-term outcomes, while the long-term effects of mobile reading and its underlying cognitive mechanisms remain underexplored. Additionally, there is a limited number of studies conducted in the context of developing countries. Therefore, the article emphasizes the multifaceted nature of mobile reading and suggests directions for future research.